(untitled) (Efficient: Indonesian Journal of Development Economics, 2026)
This study aims to determine and identify internal and external factors that affect village revenue with a case study of North Tasikmalaya including Sukaratu, Cisayong, Sukahening, Rajapolah, Jamanis, Ciawi, Sukaresik, Pagerangeung, and Kadipaten sub-districts. The method used in this research is a quantitative approach to primary data with data collection techniques using questionnaires. This research sampling technique uses Proportionate Stratified Random Sampling. The data analysis method uses the Structure Equation Model-Partial Least Square (SEM-PLS) through 3 analyses: outer model, inner model, and hypothesis testing. The results showed that human resource capacity and government policy significantly influenced village revenue. Meanwhile, community participation, accessibility, and infrastructure do not influence village revenue. The lack of community participation is due to the community’s indifference in advancing the village. Accessibility and infrastructure are also strategic issues that not all villages have adequate access and infrastructure so that regional economic development is not optimal.